2020
DOI: 10.1016/j.postharvbio.2020.111267
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome and phytohormone changes associated with ethylene-induced onion bulb dormancy

Abstract: Highlights A de novo onion transcriptome was developed to investigate dormancy transition. Continuous ethylene induced a climacteric-like respiration peak in stored onions. Ethylene upregulated ethylene biosynthesis transcripts, ACO1 , in onion baseplates. The ABA biosynthesis gene NCED was upregulated under ethylene supplementation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…7 B). Upregulation of ACO gene expression, or ACO enzyme activity, following exogenous ethylene has been described for other storage organs ( Cools et al, 2011 ; Alamar et al, 2020 ), but not for potato tubers. The transcriptomic profiles of ethylene receptors in this work showed that in potato cortex the expression of four receptor genes ( ethylene receptor_a , ethylene receptor_b , ethylene receptor_c and ethylene receptor homolog_b ) was induced by ethylene and inhibited by 1-MCP ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7 B). Upregulation of ACO gene expression, or ACO enzyme activity, following exogenous ethylene has been described for other storage organs ( Cools et al, 2011 ; Alamar et al, 2020 ), but not for potato tubers. The transcriptomic profiles of ethylene receptors in this work showed that in potato cortex the expression of four receptor genes ( ethylene receptor_a , ethylene receptor_b , ethylene receptor_c and ethylene receptor homolog_b ) was induced by ethylene and inhibited by 1-MCP ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The application of competitive ET antagonist 2,5-Norbornadiene (NBD) leads to premature sprouting in potato tubers [167]. In onion, exogenous ET not only affects the expression of ACO and receptors (EIN4 and EIL3), but also increases the accumulation of ABA by up-regulating the expression of NCED [168]. The etr1-4 mutant in birch had relative low ABA content and fast growth under SD.…”
Section: Aba and Ethylenementioning
confidence: 99%
“…At T 3 , ABA levels increased only in infected samples, showing an opposite ABA profiling in the uninfected bulbs. Plant growth hormones seemed to play a crucial role in maintaining bulb dormancy or its breakage, determining sprout elongation [ 5 , 8 , 9 , 10 , 17 ]. In particular, ABA plays a central role in all plants in biological processes related to senescence and dormancy regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In onion, dormancy occurs between bulb maturity and internal sprouting ( Figure 1 A). Several studies described the role and the crosstalk between different hormones in dormancy release, fructans mobilization, and external sprouting [ 4 , 5 , 6 , 7 , 8 ]. Abscisic acid (ABA), a growth hormone known to be involved in maturation and dormancy, accumulates during bulb growth [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation